Association of visual acuity with sleep quality and sleep duration in patients with type 2 diabetes: evidence from a cross-sectional analysis of the Fushun Diabetic Retinopathy Study - Wang, Yu; Rong, Shisong; Zhou, Zixi; Liang, Yuanbo; Lin, Zhong; Wang, Fenghua; Wang, Qitong; Feng, Kemi; Ding, Xiaoxia; Zang, Dongxiao; Li, Dong; Zang, Bo (Frontiers in Psychiatry, 2025)
ObjectiveTo examine the association between visual acuity (VA), sleep quality, and sleep duration among Chinese adults.Subjects/MethodsData were derived from the Fushun Diabetic Retinopathy Cohort Study (FS-DIRECT), a cross-sectional, community-based study conducted in Fushun, China, from July 2012 to May 2013. The study included 1284 participants (58.7% female, mean age 61.3 years) with type 2 diabetes. VA was assessed using the LogMAR chart and stratified into six groups based on LogMAR scores: <0 (optimal), 0-0.1, 0.1-0.2, 0.2-0.3, 0.3-0.5, and ≥0.5 for multivariable-adjusted analyses. Sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI).ResultsRestricted cubic splines revealed a significant J-shaped association between VA and sleep quality (P for non-linearity = 0.004). This relationship was characterized by a positive correlation for VA values below 0.5 LogMAR, with the association plateauing at higher VA levels. Compared to the optimal VA group, the odds ratios (ORs) for poor sleep quality were: 1.18 (95% CI: 1.05-1.33) for 0-0.1, 1.73 (1.52-1.97) for 0.1-0.2, 1.99 (1.74-2.28) for 0.2-0.3, 1.55 (1.33-1.80) for 0.3-0.5, and 1.80 (1.54-2.10) for ≥0.5. No significant association was found between VA and sleep duration, whether short or long, in fully adjusted models.ConclusionsOur findings reveal a J-shaped association between visual acuity and sleep quality, while no significant association was observed with sleep duration. Even mild vision changes, not typically classified as impairment, may significantly affect sleep. This underscores the importance of early sleep health consideration in eye care.